2017
DOI: 10.21315/aamj2017.22.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Antecedents for Relationship Quality Model and Its Outcomes for Priority Banking Customers in Indonesia

Abstract: To cite this article: Syafrizal, Abdul Wahid, N., and Ismail, I. (2017). Identifying the antecedents for relationship quality model and its outcomes for priority banking customers in Indonesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…Robinson and Phuong (2015) suggested that every unique culture of the organisation should follow unique approaches of CI to ensure improvement in quality. Wahid and Ismail (2017) conducted a study to identify the antecedents for relationship quality model that would help the organisations to increase the quality of their services. They found out that positive emotional expression (PEE) acts as the antecedent to relationship quality (RQ) while RQ is positively linked to the word-of-mouth (WOM) and share-of-purchase (SOP) outcomes that helps the organisations to attract and satisfy the customers through quality services (Wahid & Ismail, 2017).…”
Section: Conventional Approaches To Continuous Quality Improvementmentioning
confidence: 99%
“…Robinson and Phuong (2015) suggested that every unique culture of the organisation should follow unique approaches of CI to ensure improvement in quality. Wahid and Ismail (2017) conducted a study to identify the antecedents for relationship quality model that would help the organisations to increase the quality of their services. They found out that positive emotional expression (PEE) acts as the antecedent to relationship quality (RQ) while RQ is positively linked to the word-of-mouth (WOM) and share-of-purchase (SOP) outcomes that helps the organisations to attract and satisfy the customers through quality services (Wahid & Ismail, 2017).…”
Section: Conventional Approaches To Continuous Quality Improvementmentioning
confidence: 99%